2022
DOI: 10.1177/23259671211062225
|View full text |Cite
|
Sign up to set email alerts
|

Marking Pen Bacterial Contamination During Shoulder Surgery

Abstract: Background: Equipment used to guide surgical incisions has been shown to be a source of bacterial contamination during surgery. Purpose/Hypothesis: To compare the culture-positive rates of sterile marking pens used before and after skin preparation for shoulder surgery. It was hypothesized that there will be no difference in culture-positive rates from marking pens used after skin preparation compared with before skin preparation. Study Design: Controlled laboratory study. Methods: Overall, 43 consecutive pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In another study of ACL reconstruction surgeries, Nakayama et al demonstrated that 6% of patients had positive skin colonization near the incision site and 2% had positive graft colonization with Staphylococcus epidermidis , indicating that a surgical pen could have transmitted S. epidermidis from colonized skin to the graft [ 7 ]. In an experiment culturing pens used in shoulder reconstruction surgery, one of the 43 studied pens demonstrated growth of Propionibacterium acnes [ 8 ]. A literature review of surgical site markers as sources of infection determined that markers can be a source for cross infection with MRSA, other bacteria, fungi, or viruses [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study of ACL reconstruction surgeries, Nakayama et al demonstrated that 6% of patients had positive skin colonization near the incision site and 2% had positive graft colonization with Staphylococcus epidermidis , indicating that a surgical pen could have transmitted S. epidermidis from colonized skin to the graft [ 7 ]. In an experiment culturing pens used in shoulder reconstruction surgery, one of the 43 studied pens demonstrated growth of Propionibacterium acnes [ 8 ]. A literature review of surgical site markers as sources of infection determined that markers can be a source for cross infection with MRSA, other bacteria, fungi, or viruses [ 9 ].…”
Section: Discussionmentioning
confidence: 99%